Walking on the Pages of the Word of God Self, Land, and Text Among Evangelical Volunteers in Jerusalem - Engberg, Aron (Currents of Encounter, 2019)
In Walking on the Pages of the Word of God Aron Engberg explores the religious language and identities of Zionist evangelical volunteer workers in contemporary Jerusalem, and their stories about the religious self, the land and the biblical text. Readership: All interested in the relationship between evangelical Christianity and Israel, and scholars interested in the relationship between Christianity and Judaism, theology & anthropology, and in religion in the Middle East from theological, historical or social scientific perspectives.